1998
DOI: 10.1046/j.1365-2044.1998.329-az0482.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of intrathecal fentanyl on the characteristics of subarachnoid block for Caesarean section

Abstract: SummaryWe have assessed the effect of two induction agents on tracheal intubating conditions after rocuronium 0.6 mg.kg À1 in unpremedicated patients undergoing simulated rapid sequence induction. Following pre-oxygenation, anaesthesia was induced with propofol up to 2.5 mg.kg À1 (n 35) or etomidate 0.3 mg.kg À1 (n 36), and further increments as required. After loss of verbal contact, cricoid pressure was applied and rocuronium was injected. Laryngoscopy was performed at 45 s and intubation attempted at 60 s a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
44
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 13 publications
7
44
1
1
Order By: Relevance
“…15 But the magnitude of BP fall and use of ephedrine is similar in both the groups. These results are comparable to the findings of Khan et al, Dixit et al, Shaik et al [16][17][18] There was no change in neonatal APGAR scores among the groups, which were similar with the observations made by Hunt et al and Shendi et al 19,20 In our study, we found that Buprenorphine produced prolonged analgesia without increase in the incidence of side effects, when compared to fentanyl.…”
Section: Discussionsupporting
confidence: 92%
“…15 But the magnitude of BP fall and use of ephedrine is similar in both the groups. These results are comparable to the findings of Khan et al, Dixit et al, Shaik et al [16][17][18] There was no change in neonatal APGAR scores among the groups, which were similar with the observations made by Hunt et al and Shendi et al 19,20 In our study, we found that Buprenorphine produced prolonged analgesia without increase in the incidence of side effects, when compared to fentanyl.…”
Section: Discussionsupporting
confidence: 92%
“…None of the patients required additional anxiolytics or sedatives intraoperatively. Similar results were also reported by Shende et al 20 …”
Section: Discussionsupporting
confidence: 92%
“…Fentanyl is a lipophillic µ-receptors agonist opioid. Intrathecally, fentanyl exerts its effect by combining with opioid receptors in the dorsal horn of spinal cord and may have a supra spinal spread and action [9,10] . Pain is frequently encountered during surgery on the female genital organs under spinal local anesthetics, intrathecal fentanyl when added to spinal local anesthetics reduces significantly visceral and somatic pain and this analgesic effect has been proved by many studies [11][12][13][14] .…”
Section: Discussionmentioning
confidence: 99%